2007
DOI: 10.1007/s11738-007-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the expression of green fluorescent protein in carrot

Abstract: Green fluorescent protein (GFP) was successfully used as a visual reporter at various stages of carrot (Daucus carota L.) transformation. GFPfluorescence was non-invasively observed in protoplasts, callus and plants after the delivery of mgfp5-er gene using two transformation methods: direct DNA transfer into polyethylene glycol (PEG) -treated protoplasts and inoculation of root discs with Agrobacterium rhizogenes. Transient GFP-expression was detected in the treated protoplasts and monitored during the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Some previous reports have suggested that GFP can replace antibiotic selection (e.g. Yancheva et al, 2006;Baranski et al, 2006Baranski et al, , 2007. In our study, single green fluorescent roots could produce GFP-positive calli when maintained on media supplemented with kanamycin.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Some previous reports have suggested that GFP can replace antibiotic selection (e.g. Yancheva et al, 2006;Baranski et al, 2006Baranski et al, , 2007. In our study, single green fluorescent roots could produce GFP-positive calli when maintained on media supplemented with kanamycin.…”
Section: Discussionsupporting
confidence: 50%
“…As observed in other studies, the production of chimeric calli with green fluorescence in some, but not all, cells would be a possible outcome as a result of transgene silencing in continued culture (e.g. Baranski et al, 2007;Rakosy-Tican et al, 2007). However, as shown here, the intensity of green fluorescence of calli produced from transformed roots of the common ice plant did not change, and individual callus cells exhibited similarly high, uniform levels of GFP fluorescence even after 2 years of culture, indicating high transgene stability.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…sativus L.) cultivar ‘Koral’ were maintained in ZSMI, a modified B5 Gamborg et al. (1968) medium [B5 salts, 500 mg/l KNO 3 , 250 mg/l casein hydrolysate, 0.5 mg/l nicotinic acid, 0.1 mg/l thiamin, 0.1 mg/l pyridoxin, 20 g/l sucrose and 0.4 mg/l 2,4‐dichlorophenoxyacetic acid (2,4‐D), pH 5.7] in dark at 25°C and the protoplasts were released from well‐established cell suspension as described previously (Baranski et al., 2007b). The pGJ2350 vector was delivered into protoplasts essentially according to Radchuk et al.…”
Section: Methodsmentioning
confidence: 99%
“…GFP has proved to be a well-suited and very useful visual marker for transgenic plant screening (Baranski et al 2006(Baranski et al , 2007Borisjuk et al 1999;Elliott et al 1999;Niedz et al 1995;Tian et al 1999;Vain et al 1998;Yancheva et al 2006).…”
Section: Introductionmentioning
confidence: 99%